Euroland: Peak of the upswing – Little evidence of a new economy - Klaus-Jürgen Gern (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
In the summer of 2000, the economic expansion in Euroland has continued at a rapid pace. However, a number of leading indicators suggest that the upswing will pass its peak in the second half of this year. Several reasons are responsible for the slowdown. The European Central Bank has corrected the expansionary course after the inflationary risks in the euro area had increased; households and firms experience a reduction of real income due to the deterioration of the terms of trade; finally the export boom is coming to an end as the world economy slows down somewhat and the effects from the euro depreciation slowly fade. Real GDP will rise by 2.9 percent next year. While output growth will slow down gradually and approach the growth rate of potential output, employment will continue to expand swiftly, and the unemployment rate will decline to around 8 percent by the end of 2001. Inflation will remain above the ECB's target of 2 percent for the rest of this year and decelerate only moderately in the course of next year. While external factors will lose their impact, the core rate of inflation will remain headed upwards. The situation of public budgets seems to improve as there will be large revenues from the sale of mobile phone licenses in a number of countries. European governments intend to use these receipts to reduce public debt. The savings in terms of interest payments should also not be used to raise public spending. Sustained fiscal consolidation requires that government expenditures increase at a lower rate than GDP over an extended period of time. This is also necessary to support the course of lowering the tax burden in order to strengthen economic growth. Direct taxes will be reduced considerably in 2001, the reduction will amount to some 0.8 percent of GDP. As a consequence, structural budget deficits will rise. The increases of key interest rates can be justified on the basis of the strategy of the ECB. Since the beginning of EMU, money growth has been higher than intended. Thus, there was a need for correction. Otherwise, the risks for price level stability would have increased even more. The ECB should make sure that it will achieve its target of price level stability because this is essential for its credibility. It is also important for the attractiveness of the monetary union in general. Stability risks in Euroland did, however, not emerge because of a wrong strategy but because the strategy was not followed strictly enough by the ECB. In contrast to the situation in the United States,' there is not yet an acceleration of the increase in productivity in Euroland. However, the "new economy" will also gain ground in the euro area especially since the use of the internet is increasing rapidly. But productivity gains will remain below those observed in the US partly because the share of the computer industry is smaller. In addition, the advance of new technologies is connected with substantial structural changes in the economy. If the gains in productivity are to materialize, product and labor markets must show sufficient flexibility; this, however, is more likely in the US than in Euroland. The current weakness of the euro is usually explained by cyclical factors. Interest rate differentials as well as differences in economic growth play a key role. It can be shown that there is a close relationship between real interest rate differentials and the real exchange rate. Growth differentials do not have much additional explanatory power. On the basis of the model, a gradual appreciation of the euro towards parity vis-a-vis the US dollar is forecast.
Keywords: 330; Konjunktur; Konjunkturprognose; Wechselkurs; Europäische Wirtschafts- und Währungsunion; EU-Staaten